PATH45 Cytoskeletal and inflammatory protein biomarkers for amyotrophic lateral sclerosis. Issue 11 (22nd October 2010) - Ganesalingam, J; Lacomis, D; Lustgarten, J; Shaw, C E; Bowser, R; An, J
Abstract : Amyotrophic lateral sclerosis (ALS) is a rapidly fatal neurodegenerative disease with a typical duration of 2–5 years. Firm diagnosis is essential to intervene with disease-modifying therapies at an early stage of disease. Cytoskeletal modification and inflammation are known to occur during the pathogenesis of ALS. We measured levels of cytoskeletal proteins and inflammatory markers in the cerebrospinal fluid (CSF) of ALS cases, disease controls and healthy subjects. We determined threshold values for each protein that provided the optimal sensitivity and specificity within a training set, as determined by receiver operating characteristic (ROC) analysis. Interestingly, the optimal diagnostic was a ratio of the levels of two proteins. We next applied this test to a second set of CSF samples collected from a separate medical centre to verify our results. Overall, the predictive rule identified ALS with 87.3% sensitivity and 94.6% specificity in a total of 71 ALS subjects, 52 disease control subjects and 40 healthy control subjects. In addition, the level of one protein correlated with survival of ALS patients. We were unable to replicate these findings using plasma obtained from the same subjects. These findings support large-scale prospective biomarker studies to determine the clinical utility of diagnostic and prognostic signatures in ALS.